Sleep and other factors associated with mental health and psychological distress after intensive care for critical illness - McKinley, S.; Aitken, L.; Alison, J.; King, M.; Leslie, Gavin; Burmeister, E.; Elliott, D. (Springer-Verlag, 2012)
Purpose: Some patients who survive intensive care unit (ICU) treatment report psychological sequelae during recovery. This study examined factors associated with psychological outcomes of former ICU patients up to 6 months after hospital discharge. Methods: Participants (n = 195) were adult survivors of ICU enrolled in a multicenter trial of physical rehabilitation after hospital discharge. The 36-Item Short-Form Health Survey (SF-36), the Impact of Events Scale (IES) and the Depression, Anxiety and Stress Scales were completed, and sleep rated on a five-point scale at weeks 1, 8 and 26; clinical and demographic data were obtained from patient records. Results: Participants were 41% females with mean ± standard deviation (SD) age of 57 ± 16 years and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores of 19 ± 7; median lengths of mechanical ventilation and ICU stay were 89 h and 6 days, respectively. Impaired mental health, depression, anxiety, stress and psychological distress significantly improved after week 1. Female gender, younger age and sleeping problems were associated with impaired psychological outcomes on bivariate analyses. Age; gender; week 1 anxiety, depression and stress; week 26 sleeping; and rehabilitation study group were entered into multiple linear regression analyses for week 26 IES and SF-36 Mental Component Summary (MCS) outcomes. IES scores were associated (p < 0.05) with gender, week 1 stress and week 26 sleep but not study group; MCS scores were associated (p < 0.05) with week 1 stress and week 26 sleep but not study group.Conclusion: Female gender, early levels of increased stress and problems sleeping are associated with worse psychological recovery for survivors of critical illness.